Taking back telecom control? Governance failure, political leadership and institutional change in UK broadband policy - Manica, L.; Damásio, B.; Mendonça, S. (European Policy Analysis, 2026)
Between 2010 and 2023, the United Kingdom's broadband state-aid regime evolved from a decentralised delivery model led by local authorities to a centralised framework under Building Digital UK (BDUK) and Project Gigabit. Using historical institutionalism, multi-level governance, and Bayesian process tracing, this article analyses the political and institutional drivers of this shift. It tests three hypotheses: governance performance failure, political leadership and credit-seeking, and institutional opportunity. Drawing on National Audit Office and Public Accounts Committee reports, Ofcom data, Parliamentary debates, and departmental documents, the study finds that centralisation stemmed from inefficiencies and capacity limits in local delivery, combined with political incentives to accelerate progress and claim credit. Post-Brexit subsidy control autonomy and administrative reforms facilitated the change. The article shows how layering and conversion produced de facto governance displacement, raising normative questions on the trade-off between central efficiency and local autonomy.